Crop Water Requirements in Comparison to Actual Water Applied in Some Canal Commands of Krishna Western Delta - Srinivasulu, A; Satyanarayana, T V; Kumar, M Ravi; Sudha, JLN Sai (Journal of Agricultural Engineering, 2003)
The computer simulation model CRIWAR was applied to estimate the water requirement of kharif paddy in Srirangapuram, Mutluru and Ponnur Channel Commands under Krishna Western Delta in Andhra Pradesh for the years 2000, 2001 and 2002. In the model, the FAO modified Penman method and the Penman Monteith method for evapotranspiration calculation was used. The data of canal water released and applied were obtained from the records of the State Irrigation Department. It was found that the farmers had applied 27.2 to 57.5 %more irrigation water than required in the years 2000 and 2001 while in the year 2002, it was 10.3 to 26.6 % less than the required quantity of water. In spite of applying more water, the average yield of paddy crop in the years 2000 and 2001 was less by 10.1 to 13.2 % when compared to the year 2002 indicating that applying excess water was not beneficial. Using the 10-year average weather data, the irrigation water requirement of paddy crop was predicted for a 10-day interval throughout the crop season.